2009
DOI: 10.2337/db08-1504
|View full text |Cite
|
Sign up to set email alerts
|

CD4+CD25+ T-Cells Control Autoimmunity in the Absence of B-Cells

Abstract: OBJECTIVETumor necrosis factor ligand family members B-cell–activating factor (BAFF) and a proliferation-inducing ligand (APRIL) can exert powerful effects on B-cell activation and development, type 1 T-helper cell (Th1) immune responses, and autoimmunity. We examined the effect of blocking BAFF and APRIL on the development of autoimmune diabetes.RESEARCH DESIGN AND METHODSFemale NOD mice were administered B-cell maturation antigen (BCMA)-Fc from 9 to 15 weeks of age. Diabetes incidence, islet pathology, and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
97
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(109 citation statements)
references
References 44 publications
12
97
0
Order By: Relevance
“…Additionally, the elevated expression of MHC suggests that the presentation of antigen to T cells is enhanced, so the possibility of T cell molecular mimicry remains [10,41]. CD4 + and CD8 + T cells are critical for diabetes development, while B cells contribute to T cell priming [42][43][44][45]. RRV infection increases the number of B cell in PLN and islets and the number of CD8 + T cells in islets [13], supporting the proposed role of RRV interactions with APC in lymphocyte activation.…”
Section: Cd19mentioning
confidence: 99%
“…Additionally, the elevated expression of MHC suggests that the presentation of antigen to T cells is enhanced, so the possibility of T cell molecular mimicry remains [10,41]. CD4 + and CD8 + T cells are critical for diabetes development, while B cells contribute to T cell priming [42][43][44][45]. RRV infection increases the number of B cell in PLN and islets and the number of CD8 + T cells in islets [13], supporting the proposed role of RRV interactions with APC in lymphocyte activation.…”
Section: Cd19mentioning
confidence: 99%
“…53 Recent studies conducted by Grey and colleagues have shown that B-cell depletion delays and reduces diabetes by increasing the number of CD25 1 Foxp3 1 CD4 1 Treg T cells, thereby enforcing long-term tolerance. 54 Moreover, studies by Smith and Tedder have suggested that Breg cells, such as B10 cells, may represent a significant component of the reconstituted B-cell pool after B-cell depletion. 55 These findings suggest an involvement of Breg cells in the development of diabetes.…”
mentioning
confidence: 99%
“…Taken together with in vitro study, T cells secreted more IFN-γ and less IL-4 or IL-5 in the stimulation of BLyS, which suggest that BLyS may be a Th1 response-promoting and Th2 response-suppressing cytokine. Further studies showed that B cell reduction by BLyS blockade is accompanied by decreased frequencies of pathogenic CD4 + CD40L + T cells and reduced IL-17 levels, suggesting that BLyS levels may correlate positively with production of IL-17 [41]. We demonstrated that TACI-Ig could regulate Th cell-mediated immune responses by modulating balance of Th1/Th2 and Treg/Th17 cell in MLN of AA rats.…”
Section: Discussionmentioning
confidence: 76%